PERAN INTERAKSI SOSIAL DALAM PROSES ADAPTASI MAHASISWA PERANTAU - Hanik Maula Safitri; Binti Maunah (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the forms of social interaction, its strategic role in the adaptation process, and map the coping strategies of migrant students in the digital era. Using the library research method with inclusion criteria for scientific manuscripts from the last 10 years, data were analyzed through comparative synthesis techniques to produce an up-to-date adaptation model. The study findings indicate that social interaction plays a multidimensional role that functions as a crucial coping mechanism in alleviating culture shock and mental isolation. Specifically, interaction has now transformed into the digital realm where social media serves as a